Systematic Literature Review: Trends in Maths Learning Media for Students with Learning Disabilities - Hasanah, Aan; Afifah, Aqilah Nur; Azzahra, Rahmi Nur'aini; Aulia, Septiani; Azwar, Shiva Anugrah; Mu'afi, Yusniar Najmah (Department of Special Education, 2024)
Mathematics is a discipline that studies logic, making it challenging to teach abstract and conceptual topics to students with intellectual disabilities. This study aims to systematically review educational research related to mathematics learning media for students with intellectual disabilities using a Systematic Literature Review (SLR) methodology. The research employed the PRISMA method using Covidence software. Initially, 200 articles indexed in Google Scholar were obtained through Publish or Perish using keywords such as